Effect of resuscitative endovascular balloon occlusion of the aorta in hemodynamically unstable patients with multiple severe torso trauma: a retrospective study - Otsuka, Hiroyuki (World J Emerg Surg, 2018)
BACKGROUND: Although resuscitative endovascular balloon occlusion of the aorta (REBOA) may be effective in trauma management, its effect in patients with severe multiple torso trauma remains unclear. METHODS: We performed a retrospective study to evaluate trauma management with REBOA in hemodynamically unstable patients with severe multiple trauma. Of 5899 severe trauma patients admitted to our hospital between January 2011 and January 2018, we selected 107 patients with severe torso trauma (Injury Severity Score > 16) who displayed persistent hypotension [≥ 2 systolic blood pressure (SBP) values ≤ 90 mmHg] regardless of primary resuscitation. Patients were divided into two groups: trauma management with REBOA (n = 15) and without REBOA (n = 92). The primary endpoint was the effectiveness of trauma management with REBOA with respect to in-hospital mortality. Secondary endpoints included time from arrival to the start of hemostasis. Multivariable logistic regression analysis, adjusted for clinically important variables, was performed to evaluate clinical outcomes. RESULTS: Trauma management with REBOA was significantly associated with decreased mortality (adjusted odds ratio of survival, 7.430; 95% confidence interval, 1.081–51.062; p = 0.041). The median time (interquartile range) from admission to initiation of hemostasis was not significantly different between the two groups [with REBOA 53.0 (40.0–80.3) min vs. without REBOA 57.0 (35.0–100.0) min ]. The time from arrival to the start of balloon occlusion was 55.7 ± 34.2 min. SBP before insertion of REBOA was 48.2 ± 10.5 mmHg. Total balloon occlusion time was 32.5 ± 18.2 min. CONCLUSIONS: The use of REBOA without a delay in initiating resuscitative hemostasis may improve the outcomes in patients with multiple severe torso trauma. However, optimal use may be essential for success.